Do various personal hygiene habits protect us against influenza-like illness? - Amro K. Bin Abdulrahman; Khalid A. Bin Abdulrahman; Mansour K. Almadi; Abdulrahman M. Alharbi; Mahmoud A. Mahmoud; Mohammed S. Almasri; Tariq R. Alanazi; Rakan A. Alarifi; Abdullah A. Kilani; Omar S. Albluwi; Muaath A. Al Fraih; Yaser T. Al Otabi; et al. (BMC, 2019)
Abstract Background Several studies have reported an association between improvements in hand hygiene and the reductions in rates of intestinal parasitic diseases. However, only a some have addressed its link to the frequency of influenza-like illness. The current study aimed to find the correlation between personal hygiene habits and the frequency of influenza-like illness. Methods A cross-sectional study targeting 3000 participants conducted in Riyadh city, Saudi Arabia. A systematic random sampling methodology was applied for participant from different part of Riyadh city using a computer generating system. The researcher first started by calling each participant. A full explanation was given to each participant in details (from the purpose of the research, consent to answer the questionnaire, to the explanation of the outcome definition). Each point of the questionnaire was explained to them to make sure they had excellent comprehension, and therefore, respond accurately. Descriptive statistics and Odds Ratio and its 95% confidence intervals were used to determine the association between frequency of influenza-like illness and the studied variables. Results Two thousand eighty-two (69.4%) completed the questionnaire. The participants who spent 5-10 s in handwashing with soap and rubbing were at increased risk of more frequent influenza-like illness (odds ratio = 1.37, 1.08-1.75). Handwashing with soap and rubbing after handshaking is an independent protective habit against frequent influenza-like illness (adjusted OR = 0.59, 0.37-0.94). Conclusion The decrease of the frequency of influenza-like illness could be done through the following: getting the influenza vaccine annually, washing hands with soap and hand rubbing not less than 15 s after getting out of the bathroom, before and after handshaking and before eating. Soap companies should invent soaps that take less rubbing time to kill bacteria, and subsequently may maximize compliance in the community.